Caribbean Report 30-11-1993 - Orr, Carol (anchor); Amory, Vance (interviewee); Small, Richard (interviewee); Douglas, Denzil (interviewee); Ransome, Debbie (correspondent); Martin, Atherton (interviewee) (The British Broadcasting Corporation, 1993)
Vance Amory, Prime Minister of Nevis held discussions with both the PAM and Denzil Douglas of the St, Kitts Labour Party following the general elections in St. Kitts and Nevis. Another test case is to be taken by Jamaican lawyers to the Privy Council questioning the validity of the reclassification of death row prisoners. Delegates at the Miami Conference on the Caribbean and Latin America have been assessing the region’s chances of winning similar preferential arrangements in line with the NAFTA. The World Bank is proposing working with non-governmental organizations on projects to alleviate poverty. Over the last few days life in Cuba has been in the spotlight and the politics and legacy of past Cuban leaders José Martí and Castro has been highlighted and reexamined. France will host a conference on how to work out how to send a UN mission and a team of peacekeepers to Haiti – specifically aimed at returning exiled prisoner Jean Bertrand Aristide to power. And, Vance Amory explains his political intentions in an interview with correspondent Carol Orr.
1. Vance Amory held discussions with both the PAM and Denzil Douglas of the St, Kitts Labour Party following the general elections in St. Kitts and Nevis (00:27 - 00:56).
2. Another test case is to be taken by Jamaican lawyers to the Privy Council questioning the validity of the reclassification of death row prisoners (00:57 - 02:38).
3. Delegates at the Miami Conference on the Caribbean and Latin America have been assessing the region’s chances of winning similar preferential arrangements in line with the NAFTA - correspondent Debbie Ransome reports (02:39 -08:22).
4. The World Bank is proposing working with non-governmental organizations on projects to alleviate poverty (08:23 -10:10).
Keywords: Saint Kitts and Nevis -- Politics and government -- Elections.; Capital punishment -- Statues -- Jamaica.; Covenants -- Commerce -- Caribbean Area.; NAFTA -- Commerce -- Caribbean area -- Latin America.; World bank -- Foreign relations -- economic Aspects.; Poverty -- Foreign relations -- Economic aspects.; Cuba -- government and politics -- social aspects -- economic aspects.; united nations.; Haiti -- Politics and government -- Foreign relations -- Peace.; United Nations -- Haiti -- Peace.; Saint Kitts and Nevis -- Politics and government.; Charities -- Foreign relations -- economic Aspects.; United Nations -- France -- Peace.